Montaigne E A Ideia De Conferência - Fajardo, Victoria Brites [UNIFESP] (2017)
This paper has as its main objective the analysis of the Chapter VIII, De l'art conférer, the third book of the work of Michel de Montaigne, ‘The Essays’. Our starting point will be the analysis of the Renaissance’s interpreters so that we can read the essay within their culture ambience. After the presentation of the context in which Montaigne lived, we will work the idea of conference and insist on the use of this term, not conversation, from which it will draw two fundamental ideas, will be extracted: the use and value of the counter example; And the primacy of form over content. To explore these ideas, we will resort to other essays that work on the same theme, whose goal is the ethical transformation of readers.